2012
DOI: 10.1093/icb/ics087
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics to Assess the Role of Phenotypic Plasticity in Aquatic Organisms Exposed to Pollution and Global Warming

Abstract: Nowadays, the unprecedented rates of anthropogenic changes in ecosystems suggest that organisms have to migrate to new distributional ranges or to adapt commensurately quickly to new conditions to avoid becoming extinct. Pollution and global warming are two of the most important threats aquatic organisms will have to face in the near future. If genetic changes in a population in response to natural selection are extensively studied, the role of acclimation through phenotypic plasticity (the property of a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 94 publications
0
26
0
Order By: Relevance
“…The observed proteome level acclimatory response to warming is likely to be an important determinant of the effects of projected regional and/or global warming scenarios on C. gigas. Such a short-term acclimation and phenotypic modification at proteome level would allow organisms to slightly shift its salinity and/or temperature optimum for different physiological activities (Silvestre et al, 2012). The mechanisms that driving the observed correlation between the proteome change and the physiological processes are not fully understood but are likely involved variety of temperature mediated elevated activates of enzyme production, transcriptional and translational regulation (Anestis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed proteome level acclimatory response to warming is likely to be an important determinant of the effects of projected regional and/or global warming scenarios on C. gigas. Such a short-term acclimation and phenotypic modification at proteome level would allow organisms to slightly shift its salinity and/or temperature optimum for different physiological activities (Silvestre et al, 2012). The mechanisms that driving the observed correlation between the proteome change and the physiological processes are not fully understood but are likely involved variety of temperature mediated elevated activates of enzyme production, transcriptional and translational regulation (Anestis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, characterization of proteins involved in larval metamorphosis is required to predict both the short-term acclimation and longterm adaptive capacity of oysters to climate change. In the past decade, there has been an exponential growth in the use of mass spectrometry as a versatile tool in large-scale environmental proteomics studies (Silvestre et al, 2012;Slattery et al, 2012;Timmins-Schiffman et al, 2014). For example, OA was shown to reduce the expression of several proteins to conserve energy, but induced oxidative stress especially in cytoskeletal proteins (Tomanek et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that an isozyme is a product of gene expression, it can be a biochemical indicator of stress tolerance and exhibit heritability and molecular variance. According to Silvestre et al (2012), proteome is a link between genotype and phenotype and a central factor of cellular phenotype. In human cells, cadmium induced genes which are related to cellular protection and detoxification mechanisms.…”
Section: Enzyme Plasticitymentioning
confidence: 99%
“…This article accents the significance of proteomics as a tool for determination of toxic effects of environmental stressors. Besides, these studies tend to integrate proteomics, genomics, and metabolomic informations and explain fundamental physiological processes which enable organisms to interact with new environments (Garcia-Reyero and Perkins 2011; Silvestre et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An examination of the early stage of diatom cell death in natural communities is required to better understand protein cycling prior to microbially catalyzed degradative processes. Proteomic studies on plant programmed cell death (Chivasa et al 2011, Choi et al 2011) and algal cell stress (Jamers et al 2009, Silvestre et al 2012 have identified potential indicators and regulators of proteomic alteration. In the Bering Sea, ice retreat modulates the highly productive, but temporally constrained spring bloom, which facilitates tracking of potential algal population markers for cell death and subsequently bloom termination.…”
Section: Introductionmentioning
confidence: 99%